Geotechnical characterisation of marine clay as potential liner material - Rahman, Z.A.; Yaacob, W.Z.W.; Rahim, S.A.; Lihan, T.; Idris, W.M.R.; Mohd Sani, W.N.F. (Universiti Kebangsaan Malaysia, 2013)
Natural clay is commonly used as a liner material to contain landfill leachate from contaminating the environment. A key characteristic of liner material is its hydraulic conductivity. It is recommended that the hydraulic conductivity of the potential liner material should be of 1×10-9 m/s or less. This paper presents the geotechnical characteristics of marine clay that may be used as landfill liner material. The tests were consistency index, compaction behaviour, compressibility and hydraulic conductivity. The marine clay was dominated by finer fraction of silt and clay (78%-88%) followed by sand (12%-22%). The clay minerals commonly present were montmorillonite, kaolinite and illite as well as quartz as the non-clay mineral. The consistency index for the liquid limit, wL and plastic limit, wP were 56.6%-80.5% and 36%-45%, respectively. The plastic index, Ip of the marine clay samples ranged from 19% to 37%. The permeability test indicated that the hydraulic conductivity of the samples ranged between 1.10 × 10-9 and 2.44 × 10-9 m/s. The very low permeability showed by the marine clay can be related to the presence of high content of finer fraction. Compaction of marine clay samples resulted in maximum dry density, ρdmax that ranged between 1.5 and 1.6 g/cm3 and optimum moisture content, wopt that ranged between 18.2% and 25%. During the consolidation of the marine clay, the hydraulic conductivity decreased within the recommended permeability for landfill liners. This study showed that some geotechnical characteristics of the studied marine clay were in favour of being used as landfill liner material.